Ginkgolide injections in meglumine, combined with edaravone, significantly increases the efficacy in acute ischemic stroke: A meta-analysis - Yan, Mingyuan; Wu, Jing; Wang, Le; Wang, Kaiyue; Li, Lili; Sun, Tianye; Zhang, Han; Zhang, Mi; Zou, Lin; Yang, Songyi; Liu, Jinmin (Frontiers in Pharmacology, 2024)
Except for intravenous thrombolysis, the effectiveness of western drugs for the treatment of acute ischemic stroke seems to be limited, and we are committed to investigate the effect of diterpene ginkgolides meglumine injection (DGMI) combined with edaravone on acute ischemic stroke. Methods: PubMed, Cochrane Library, Web of Science, CNKI, WanFang, VIP, and CBM databases were searched up to June 2023, data were analyzed using both fixed-effects and random-effects models by Review Manager. For each outcome, the mean difference (MD) with a 95% confidence interval (CI) was calculated. Results: Eighteen studies with 1,636 participants were included in this study. The DGMI group not only significantly reduced NIHSS (